PERTANGGUNG JAWABAN PIDANA PENGURUS KORPORASI TERKAIT TINDAK PIDANA PERDAGANGAN ORANG - Faisol Faisol (Fakultas Hukum Universitas Islam Malang, 2019)
ABSTRACTHuman Trafficking is a slavery in modern era. The crime of human trafficking is no longer a regional crime but has a turned into a global crime. At first this type of crime is only commited by individuals but as the economic development and cooperation relations between countries, the crime trafficking in person develops both in quality and quantity. Following up the issue, constitution no. 21 of 2007 has been made concerning the Eradication of Trafficking in Persons. The corporation which is involved in human trafficking crime, the criminal responsibility and punishment may be imposed directly on corporations and/or to corporate administrators as organs conducting corporate activities.Key words: Human Trafficking, Corporate, Corporate administrators Criminal LiabilityÂ ABSTRAKPerdagangan orang merupakan sebuah perbudakan dizaman modern. Kejahatan perdagangan orang bukan lagi kejahatan yang bersifat regional melainkan telah berubah menjadi kejahatan yang bersifat global. Pada awalnya jenis kejahatan ini hanya dilakukan oleh perorangan namun seiring berkembangnya perekonomian dan hubungan kerja sama antar negara, kejahatan perdagangan orang mengalami perkembangan baik secara kualitas maupun kuantitasnya. Menidndak lanjuti permasalahan tersebut maka dibuatlah Undang-Undang No. 21 Tahun 2007 tentang Pemberantasan Tindak Pidana Perdagangan Orang. Korporasi yang terlibat dalam tindak pidana Perdagangan orang maka untuk pertanggungjawaban pidana dan pemidanaannya dapat dijatuhkan langsung kepada korporasi dan/atau kepada pengurus korporasi selaku organ yang menjalankan kegiatan korporasi.Kata Kunci: Perdagangan Orang, Korporasi, Pertanggungjawaban Pidana Pengurus Korporasi